How to draw tattoo style : featuring projects by real tattoo artists - Fish, Andy (Dover Publications, 2014)
A great tattoo starts with a great tattoo drawing. Whether you want to become the next big tattoo artist, want to perfect a design for yourself, or just like to create new and original tattoo art, How to Draw Tattoo Style is the book for you. Filled with fascinating historical background and designs that range from "old school" nautical motifs to tribal and Oriental styles, the book offers expert tips on creating professional tattoo flash of skulls, hearts, dragons, and other images. You'll be drawing terrific tattoos in no time!